2020
DOI: 10.1002/ppsc.202000108
|View full text |Cite
|
Sign up to set email alerts
|

New Prospects for Particle Characterization Using Analytical Centrifugation with Sector‐Shaped Centerpieces

Abstract: Analytical centrifugation (AC) has recently shown great potential for the accurate determination of particle size distributions. The well‐established LUMiSizer(R) is customized by a new design allowing for higher rotor speeds, improved thermal insulation, and measurement cell assembly. The latter enables sedimentation analysis of nanoparticles (NPs) in sector‐shaped centerpieces. The measurement window of AC experiments is assessed by the Peclet (Pe) number. It is shown that at low Pe numbers (0.7 < Pe <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Moreover, the recent development of sector-shaped centerpieces for AC experiments enabled the measurement of a full diffusion-corrected sedimentation coefficient distribution. With this, it is possible to determine the hydrodynamic diameter distribution and the core-diameter distribution of gold nanoparticles alongside the stabilizer shell thickness of 3 nm only (Uttinger et al, 2020). (Huynh et al, 2016).…”
Section: D Analysis By Analytical Ultracentrifugationmentioning
confidence: 99%
“…Moreover, the recent development of sector-shaped centerpieces for AC experiments enabled the measurement of a full diffusion-corrected sedimentation coefficient distribution. With this, it is possible to determine the hydrodynamic diameter distribution and the core-diameter distribution of gold nanoparticles alongside the stabilizer shell thickness of 3 nm only (Uttinger et al, 2020). (Huynh et al, 2016).…”
Section: D Analysis By Analytical Ultracentrifugationmentioning
confidence: 99%
“…It is reported that such convective instabilities arise primarily due to (i) temperature gradients across the cuvette, and (ii) rectangular shaped sample cell. Uttinger et al [61] reports presence of temperature gradients of 0.1-50 mK across the sample cell, at higher instrument operation temperatures, which might lead to convective rolls for nanoparticle suspensions over long experimental times. In order to reduce the effect of lateral temperature gradients, all measurements were performed at low temperature (~10 °C).…”
Section: Dispersion Characteristics 421 Sedimentation Fingerprintsmentioning
confidence: 99%
“…It is reported that such convective instabilities arise primarily due to (i) temperature gradients across the cuvette and (ii) rectangular shaped sample cells. Uttinger et al [60] recently reported the presence of temperature gradients of 0.1-50 mK across the sample cell, at higher instrument operation temperatures, which might lead to convective rolls for nanoparticle suspensions over long experimental times. In order to reduce the effect of lateral temperature gradients, all measurements were performed at low temperatures (~10 °C).…”
Section: Rheological Characterizationmentioning
confidence: 99%